LANGUAGE VARIATION IN BALI: THE DIALECT DIFFERENCES BETWEEN BULELENG’S DIALECT AND KARANGASEM’S DIALECT - Gusti Agung Bili Wiliawan (English Department, STKIP PGRI Bandar Lampung, 2021)
Knowing that there is a big distinction between Buleleng's dialect and Karangasem's dialect, it is interesting to discover what are the differences between these dialects. This writing will help readers to get insight about this topic as well as other researcher will get such a reference. Data were collected through observing and understanding the concepts of the determined topic. The data were further analyzed through triangulation by other supporting references. Main focus of this writing is distinguishing the Buleleng's dialect and Karangasem's dialect. Differences can be seen through 3 aspects, namely word choices, syntaxis, and pronunciation.